THE INFLUENCE OF SOCIAL MEDIA IN THE SPREAD OF POLARIZATION AND PEACE COUNTER-NARRATIVE EFFORTS IN INDONESIA - Jundan Restu Alam; Lukman Yudho Prakoso; Yulian Azhari; Rachmat Setiawibawa; Arifuddin Uksan (Yayasan Amanah Nur Aman, 2025)
This study analyzes the dual role of social media in driving social polarization and peaceful counter-narrative efforts in Indonesia. Using a qualitative approach and literature study of secondary data, this research examines the mechanisms of social media as an accelerator of polarization and evaluates the effectiveness of counter-narrative strategies. The results indicate that polarization is accelerated by the spread of hoaxes, algorithmically reinforced echo chambers, and the exploitation of identity politics, all of which threaten national integration. On the other hand, social media also proves to be an effective tool for peaceful counter-narratives, as demonstrated by case studies of the Peace Ambassador Communities in East Kalimantan and West Java. The success of their strategies lies in contextualizing narratives of nationalism, religious moderation, and humanity. The study concludes that the effectiveness of counter-narratives is highly dependent on cross-sector collaboration and the improvement of standardized digital literacy to build societal digital resilience.